Titanium-doped multilayer copper-based composite material and preparation method thereof

By introducing a titanium doped layer into the copper-based composite material, the interface combination between the enhanced phase and the copper matrix is ​​improved, and the problem of insufficient mechanical properties and friction properties of existing copper alloys is solved, and higher mechanical properties and durability are achieved .

CN116213731BActive Publication Date: 2025-02-21CHENGDU TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211711318.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-02-21
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The mechanical properties, friction properties and durability of existing copper alloys are difficult to meet expectations, and the interface bond between the enhanced phase and the copper matrix is ​​poor.

Method used

Copper-based composite materials with titanium-doped multilayer structure are used to improve interface bonding performance by setting a titanium-doped layer between the enhanced phase composite layer and the copper-based surface layer, and the interface bonding performance is improved by designing the multi-layer structure. Play a coordinated role in enhancing phases.

Benefits of technology

It significantly improves the mechanical properties and friction properties of copper-based composite materials, improves the interface combination between the enhanced phase and the matrix, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116213731B_ABST
    Figure CN116213731B_ABST
Patent Text Reader

Abstract

The present invention relates to a titanium-doped multilayer copper-based composite material, comprising a titanium-doped layer, a reinforcement phase composite layer, and a copper-based surface layer; the reinforcement phase composite layer is at least one of an aluminum oxide whisker reinforcement layer and a graphene reinforcement layer; the copper-based surface layer is located at the top and bottom layers of the composite material; the titanium-doped layer is arranged between adjacent reinforcement phase composite layers, or between the reinforcement phase composite layer and the copper-based surface layer. In the titanium-doped multilayer copper-based composite material of the present invention, as the titanium content of the titanium-doped layer increases, the mechanical properties of the multilayer copper-based composite material are significantly improved, the titanium-doped layer structure realizes the continuous reinforcement of the multilayer structure, improves the interface bonding force of the reinforcement phase, realizes the anisotropy in the direction perpendicular to the multilayer structure, and has good friction performance and electrical conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy materials, and in particular to a copper-based composite material with a titanium-doped multilayer structure and a preparation method thereof, in which the electrical and mechanical properties of the copper-based composite material are improved by utilizing the layered structure. Background Art

[0002] Copper and copper alloys are widely used in daily life and production as well as some high-precision instruments due to their excellent physical properties, such as aerospace, marine shipping, electrical engineering precision instrument parts, etc. Although copper and copper alloys have many advantages, they also have some disadvantages, such as poor interface bonding strength between the reinforcement and the copper matrix, resulting in poor mechanical properties or failure to achieve the expected results. For example, copper has excellent electrical properties, but copper is relatively soft. In some cases where large currents need to be carried and there is a certain relative displacement, the friction performance and durability performance are poor.

[0003] Copper-based composite materials are special materials modified from copper or copper alloys. They also have excellent mechanical and chemical properties and are often used as substitutes for traditional copper / copper alloys. In existing research, various reinforcement phases are often used to prepare copper-based composite materials to meet the needs of different application scenarios. However, the interface bonding between the reinforcement and the copper matrix is ​​usually poor, making it difficult to significantly improve the performance of the composite material. Summary of the invention

[0004] The purpose of the present invention is to provide a titanium-doped multilayer copper-based composite material to address the problems in the prior art that the mechanical properties, friction properties and durability of copper alloys do not meet expectations, and the combination of the reinforcement phase and the copper-based composite material is poor.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A titanium-doped multilayer copper-based composite material, comprising a titanium-doped layer, a reinforced phase composite layer, and a copper-based surface layer;

[0007] The reinforced phase composite layer is at least one of an aluminum oxide whisker reinforced layer and a graphene reinforced layer;

[0008] The copper-based surface layer is located at the uppermost layer and the lowermost layer of the composite material;

[0009] The titanium doped layer is arranged between adjacent reinforced phase composite layers, or between the reinforced phase composite layer and the copper-based surface layer.

[0010] The titanium-doped multilayer copper-based composite material of the present invention uses copper alloy as the main structural unit, and is formed into a multilayer copper-based composite material by stacking and combining multiple copper-based layered structures, maximizing the mutual coordination of different reinforcement phases, and achieving better comprehensive performance of the multilayer copper-based composite material. In particular, a titanium-doped layer is set between adjacent reinforcement phase composite layers and between the reinforcement phase composite layer and the copper-based surface layer, and the interface bonding performance of the copper-based nanocomposite material is improved by titanium doping diffusion. Due to the metal titanium doping, the graphene layer and the aluminum oxide whisker layer of the reinforcement phase can have a better solid solution effect, and the mechanical properties of the reinforcement phase material can be improved more stably and significantly, and it is not easy to be limited by the failure of the bonding interface.

[0011] Moreover, the titanium-doped layer can form the main phase of the copper-titanium alloy, which is evenly distributed after being fully diffused and dispersed, forming a doped interface with a stable and continuous thickness, thereby improving the interfacial bonding performance between the reinforcement phase and the matrix. Under the mediation of the titanium-doped layer, various reinforcement phase layers achieve excellent performance (such as the high conductivity and corrosion resistance of the copper graphene layer, the high hardness and high-temperature stability of the copper aluminum oxide whisker layer). The titanium-doped layer in the composite material effectively blocks the microcracks generated at the reinforcement phase interface, thereby improving the fracture toughness and strength of the copper-based nanocomposite material, and preventing the problem of failure of the reinforcement phase to bond with the matrix.

[0012] Furthermore, the thickness of the titanium-doped layer, the reinforcement phase composite layer, and the copper-based surface layer are independent of each other and are all within the range of 0.5-3 mm. Preferably, the thickness of each layer is 0.5-2.1 mm, especially 1.2-2.1 mm. The layered titanium-doped copper layer optimizes the interface bonding performance of the reinforcement phase-doped copper layer. An overly thick single-layer design cannot be used. The appropriate thickness can better allow the diffusion of alloy elements between the multiple layers to occur.

[0013] It is best to control the thickness of each layer to be 1.4-2.1 mm. Experiments have found that when the thickness of each layer is within this range, the titanium-doped layer and the reinforcement phase layer cooperate well, the reinforcement phase can maximize its reinforcement effect, and the titanium-doped layer can fully ensure the bonding stability and reliability of the reinforcement phase layer.

[0014] Furthermore, the titanium-doped multilayer copper-based composite material is provided with the following structural layers from bottom to top: a first copper-based surface layer, a second titanium-doped layer, a third graphene-enhanced layer, a fourth titanium-doped layer, a fifth aluminum oxide whisker-enhanced layer, a sixth titanium-doped layer, and a seventh copper-based surface layer. The first layer to the seventh layer are the order in which the film layers are arranged, and a titanium-doped layer is arranged between each layer of the reinforced phase composite layer or between the reinforced phase composite layer and the copper-based surface layer, forming an organic fusion composite material with a layered structure.

[0015] The copper-based composite material has a graphene reinforcement layer and an aluminum oxide whisker reinforcement layer, a titanium-doped copper layer structure is sandwiched between adjacent reinforcement phase-doped copper layers, and a titanium-doped layer is also provided between the reinforcement layer and the copper-based surface layer. The titanium-doped layer forms a copper-titanium alloy, which has the following effects on the adjacent layers: (1) ensuring the specific excellent properties of the copper and reinforcement phase layers, such as the high conductivity and corrosion resistance of the copper graphene layer, and the high hardness and high-temperature stability of the copper aluminum oxide whisker layer; (2) the titanium element doped in the copper-titanium layer can diffuse in the multi-layer direction under the action of chemical potential, thereby playing an interface doping role on the various components in the copper and reinforcement phase layers, and improving the interface bonding performance between the reinforcement phase and the matrix; (3) effectively blocking the expansion path of microcracks that may be generated in the copper and reinforcement phase layers, thereby improving the fracture toughness and strength of the composite material. Therefore, by setting the titanium-doped layer at intervals, the function of the reinforcement phase components can be better exerted and a longitudinal anisotropic composite material with a multi-layer structure can be realized.

[0016] The copper-based surface layer included at the top and bottom of the copper-based composite material realizes the sealing of the pure copper layer, which ensures the surface consistency of the composite material when the material is formed, and the overall hot pressing sintering consistency of the composite material is excellent.

[0017] Furthermore, the titanium doped layer is a copper-titanium alloy layer doped with 1-6% titanium element. 1-6% titanium powder is added to pure copper powder, mixed and sintered. Preferably, the titanium doped layer is a copper-titanium alloy layer doped with 2-5% titanium element.

[0018] Further, the reinforced phase composite layer is a composite layer with copper as the main body and 0.2-2% of the reinforced phase material. For example, an alumina whisker reinforced layer is formed by mixing 0.2-2% alumina whiskers and pure copper powder and hot pressing and sintering. Alternatively, a graphene reinforced layer is formed by mixing 0.2-2% graphene and pure copper powder and hot pressing and sintering. Preferably, the amount of graphene in the graphene reinforced layer is 0.2-1.5%.

[0019] The proportions of the reinforcement phase or doped titanium are all weight percentages, and the main material is copper.

[0020] Furthermore, the copper-based surface layer is formed by hot-pressing and sintering pure copper powder.

[0021] The copper-based composite material of the present invention has a multilayer structure and can be used to prepare friction materials and heat sink materials such as brake pads, conductive sliders, brushes, etc. The layered structure enables the material to have better interlayer heterogeneity, which can not only ensure good structural mechanical strength, but also give full play to the specific properties of the reinforced phase material, such as corrosion resistance, conductivity, self-lubrication, high hardness, high temperature stability and other characteristic advantages, to achieve the application of composite materials with long-term weather resistance.

[0022] The present invention also provides a method for preparing the above-mentioned titanium-doped multilayer copper-based composite material, by preparing the raw materials of the titanium-doped multilayer copper-based composite material layer by layer through relevant processes, and forming it through a suitable hot pressing and sintering process to achieve an anisotropic copper-based composite material, which has the performance advantages of special conductive and friction application environments.

[0023] A method for preparing the titanium-doped multilayer copper-based composite material comprises the following steps:

[0024] S1. Weigh the raw materials of the titanium doped layer, the aluminum oxide whisker reinforcement layer and the graphene reinforcement layer according to the designed proportion;

[0025] The aluminum oxide whisker and copper powder are mixed evenly to obtain an aluminum oxide whisker reinforcement layer raw material;

[0026] The graphene and copper powder are mixed evenly to obtain a graphene reinforcement layer raw material;

[0027] Mixing titanium powder and copper powder evenly to obtain a titanium doped layer raw material;

[0028] Add the above raw materials into alcohol respectively, completely submerge the materials, and perform ultrasonic dispersion treatment.

[0029] S2. After the ultrasonic treatment, the raw material powders are respectively loaded into agate jars for ball milling; the preferred ball-to-material ratio used in the ball milling process is 3:1; alcohol is added to ensure that the alcohol submerges the bottom layer of agate balls but does not submerge all the agate balls.

[0030] S3. After the ball milling is completed, take out the raw materials and rinse the agate balls with alcohol, and combine the raw material powders.

[0031] S4, placing the raw material powder in a culture dish, and letting it stand to evaporate to remove the alcohol (preferably, the alcohol is evaporated by natural air drying for more than 24 hours); when the raw material powder in the culture dish is dried to a state where the particles are distinct, cover the culture dish with plastic wrap;

[0032] Poke at least one hole in the plastic wrap and place the raw powder along with the petri dish into the freeze dryer to freeze dry.

[0033] S5. After freeze drying, a layer of pure copper powder is spread on the bottom of the mold and the powder is compacted; then titanium doping layer raw material, aluminum oxide whisker reinforcement layer raw material, titanium doping layer raw material, graphene reinforcement layer raw material, titanium doping layer raw material, and pure copper powder are added in sequence; after each addition of raw materials, compaction is performed to ensure that the materials are compacted and flat;

[0034] Except for pure copper powder, the thickness of each layer of titanium doped layer raw material, aluminum oxide whisker reinforcement layer raw material, and graphene reinforcement layer raw material does not exceed 2-5 mm. Preferably, the thickness of each layer is controlled between 0.5-3 mm. Preferably, the thickness of each layer is 1.4-2.1 mm.

[0035] S6, hot pressing sintering, the sintering process is as follows:

[0036] First, evacuate to below 20Pa, then heat to 290-325℃ at a rate of 5-15℃ / min (preferably 10℃ / min), keep warm for 5-25min; then heat to 920-945℃ at a rate of 5-15℃ / min;

[0037] At the same time, when the temperature reaches 640-655℃, gradually increase the pressure, and maintain the pressure when the pressure reaches 20Mpa; when the temperature rises to 930℃±10℃, keep the temperature and pressure and sinter for 2-2.5 hours;

[0038] After the heat preservation and pressure sintering is completed, turn off the heating power supply and cool down with the furnace; when the temperature cools to 650-750℃, turn off the pressurization;

[0039] Then, after the temperature drops to room temperature, all power supplies are turned off, and after 12-24 hours, the furnace is opened to take samples to obtain a titanium-doped multilayer copper-based composite material.

[0040] Furthermore, in step S2, the ball milling speed is 300 rpm, and the ball milling is performed for 2-4 hours; preferably, the ball milling process is performed in forward rotation for half of the time and in reverse rotation for half of the time.

[0041] The present invention uses a method of pre-ultrasonic dispersion and mixing with copper powder to pre-mix the materials, improve the material mixing efficiency, reduce the defects of mutual agglomeration of materials, control each reinforcement phase material in a specific structural layer raw material, and remove the auxiliary agent anhydrous ethanol in the process of mixing powder materials through freeze drying. Finally, hot pressing sintering is performed according to a certain procedure to obtain a high-quality titanium-doped copper-based composite material.

[0042] Furthermore, in S1, the amount of anhydrous ethanol is sufficient to submerge the material, and the ultrasonic treatment is performed for 20-40 minutes. Anhydrous ethanol, as an ultrasonic auxiliary agent, has a good wetting and dispersing effect, and is easily evaporated and removed later.

[0043] Furthermore, in S2, the ball-to-material ratio used in the ball milling process is 3: 1. Alcohol is added to ensure that the alcohol submerges the bottom layer of agate balls but does not submerge all the agate balls.

[0044] Preferably, in S2, the ball milling speed is 300 rpm, and the ball milling is performed for 2-4 hours. Preferably, the ball milling process is performed in forward rotation for half of the time and in reverse rotation for half of the time, and the forward rotation and reverse rotation are performed alternately.

[0045] Furthermore, in S3, the alcohol is evaporated and removed by natural air drying for more than 24 hours. The raw material powder is placed in a culture dish and allowed to evaporate and remove the alcohol. Active ventilation can also be used to promote the volatilization and removal of alcohol, but the powder must not be blown away or dropped.

[0046] Preferably, in S4, the freeze-drying time is preferably ≥ 24 hours.

[0047] Furthermore, in S5, each time the material is added to the mold, it is compacted and pressed to ensure that each layer is formed in the correct position during the hot pressing and sintering process.

[0048] Furthermore, in S6, the hot pressing sintering temperature is 930°C±10°C, the heat preservation time is 2h±1h, and the sintering pressure is 20.0MPa±2MPa.

[0049] Preferably, during the hot pressing sintering process, the temperature and pressure are controlled as follows: firstly, the temperature is raised to 300°C±10°C at a rate of 10°C / min±5°C, and then kept at this temperature for 5-20 minutes, preferably 10 minutes.

[0050] Then, the temperature is raised to about 650℃±10℃ at the same heating rate, and pressurization is started. Then, the temperature is heated to 930℃±10℃ at the same heating rate, and after keeping warm for 2h±1h, the temperature is cooled (annealed) with the furnace. When the temperature is cooled to 650-750℃, pressurization is turned off.

[0051] After the temperature drops to room temperature, all power supplies are turned off. After 12-24 hours, the furnace is opened for sampling to obtain a titanium-doped multilayer copper-based composite material.

[0052] Furthermore, in step S6, in order to avoid accidents during the hot pressing sintering process, graphite paper may be placed in the sintering mold to prevent the inner wall of the mold from directly contacting the composite powder and causing adhesion that makes it difficult to remove.

[0053] The titanium-doped copper-based nanocomposite material of the present invention adopts ultrasonic mixing and ball milling of copper powder, graphene, titanium powder, and aluminum oxide whiskers, takes the reinforcing phase as the skeleton structure, and uses titanium doping as auxiliary fusion, and cooperates with the temperature and pressure program control during the hot pressing sintering process to prevent the grain growth, thereby achieving the mechanical property enhancement effect of improving tensile strength and toughness. The structural stress is eliminated by furnace cooling annealing, and the dispersion strengthening distribution of the reinforcing phase is maintained, so that the comprehensive performance of the material reaches the best state. The results of various mechanical tests such as material tension and compression show that the doping component of the copper-based nanocomposite material has a significant promoting effect, which can meet the requirements of a variety of special application environments.

[0054] Further, in step S4, after the raw material powder and the culture dish are placed in the freeze dryer, pay attention to observation in the first half hour. If there is residual alcohol in it that will cause powder spraying, the machine needs to be stopped in time, the raw material powder needs to be taken out, and natural air drying or active air drying treatment needs to be continued.

[0055] The method of the present invention adopts a powder metallurgy method to firstly mix copper powder, graphene, titanium powder, and alumina whiskers by ultrasonic mixing, and then perform ball milling treatment, so that the ceramic reinforcement alumina whiskers and copper powder, graphene and copper powder are respectively mixed evenly, and the reinforcing phase can not only realize the skeleton reinforcement effect, but also prevent the grain from increasing, and as an obstacle, the grain is refined to achieve the mechanical property enhancement effect of improving tensile strength and toughness. At the same time, various reinforcing phases / doping phases and copper powder are fully mixed evenly to obtain a mixed material with finer and more uniform reinforcing phase / doping phase particles, and then freeze-dried to maintain the uniform mixing state of the raw materials during the ball milling process, so as to achieve a better dispersion strengthening effect.

[0056] According to the multi-layer structure design, ball-milled mixed materials are prepared separately, loaded into molds and hot-pressed and sintered. After layered compaction treatment, the doped phase and the reinforced phase are fully integrated in the copper-based material and arranged in a designed order to form a whole to be sintered, thereby achieving high-quality bonding of the doped phase and the reinforced phase with the copper matrix, controlling the layered position arrangement of the multi-layer structure, and achieving high-efficiency reinforcement effect of titanium-doped multi-layer copper-based composite materials through efficient fusion promotion.

[0057] The obtained copper-based composite material is made into samples of various sizes by wire cutting, and various mechanical tests such as stretching and compression are carried out. The experimental results show that the layered structure of the copper-based composite material of the present invention is well fused and enhanced during the hot pressing sintering process, and the doping layer and the reinforcement phase layer with appropriate thickness are controlled to promote each other. The copper-based performance of the multi-layer structure is good, and the mutual reinforcement of the multi-layer material is better achieved. Compared with the process method of directly mixing the titanium doping phase and multiple reinforcement phase components, the layered structure composite material shows better mechanical properties and surface properties, and has the potential to be applied in environments with special surface performance requirements.

[0058] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0059] 1. In the titanium-doped multilayer copper-based composite material of the present invention, as the titanium content of the titanium-doped layer increases, the mechanical properties of the multilayer copper-based composite material are significantly improved. The titanium-doped layer structure realizes the continuous enhancement of the multilayer structure, improves the interface bonding force of the reinforced phase, realizes the anisotropy in the direction perpendicular to the multilayer structure, and has good friction and electrical conductivity. For example, the hardness of the 4% titanium content sample increased by 46.68% compared with the 1% sample, the average compressive strength increased by 34.04%, and the average tensile strength increased by 448.38%. The addition of the Ti element significantly improves the mechanical properties of the composite material.

[0060] 2. The strengthening mechanism of the titanium-doped multilayer copper-based composite material of the present invention includes the dispersion strengthening effect of nano-aluminum oxide whiskers and the fine grain effect of acting as an obstacle to prevent grain growth, while graphene as a uniformly distributed second phase improves the interface effect and enhances the load transfer effect. In addition, the titanium-doped layer in the multilayer structure, as a sandwich structure with alternately arranged reinforcement phases, plays a role in integrating the multilayer structure and further improving the anisotropy, avoiding the risk of interlayer failure of anisotropic materials, and achieving the dense continuity of multiple reinforcement phase materials perpendicular to the layering direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 It is a schematic diagram of the process flow of the present invention.

[0062] Figure 2 It is a schematic diagram of the layered structure of a multilayer titanium-doped multilayer copper-based composite material.

[0063] Figure 3 The present invention is a schematic diagram of the hot pressing sintering program setting in the preparation process of the titanium-doped multilayer copper-based composite material.

[0064] Figure 4 It is a schematic diagram of the structural dimensions of the tensile strength test workpiece.

[0065] Figure 5 It is the XRD test diagram of each layer of raw material powder.

[0066] Figure 6 Four points were selected on the longitudinal surface of the sample for micro-area XRD detection spectrum.

[0067] Figure 7 The material of alumina whiskers and copper powder is ball-milled and then freeze-dried, scanning electron microscope image.

[0068] Figure 8 This is a scanning electron microscope image of a mixed powder of alumina whiskers and copper powder.

[0069] Fig. 9 This is a scanning electron microscope image of a mixture of graphene powder and copper powder.

[0070] Fig.10 This is a SEM scanning electron microscope image of a powder mixture of titanium powder and copper powder.

[0071] Fig.11 It is the XRD spectrum of the graphene-reinforced copper layer of the multi-layer titanium-doped multi-layer copper-based composite material obtained by sintering.

[0072] Fig.12 It is the XRD spectrum of the titanium-doped copper layer of the multi-layer titanium-doped copper-based composite material obtained by sintering, and the element analysis EDS.

[0073] Fig.13This is the backscattered EDS analysis of the copper-aluminum oxide layer.

[0074] Fig.14 is the compressive load-displacement of 1% titanium-doped multilayer copper matrix composite sample.

[0075] Fig.15 is the compressive load-displacement of 4% titanium-doped multilayer copper matrix composite sample.

[0076] Fig.16 This is the tensile force-displacement diagram of the 1% titanium-doped multilayer sample prepared in Example 1.

[0077] Fig.17 This is the tensile force-displacement diagram of the 4% titanium-doped multilayer sample prepared in Example 2.

[0078] Fig.18 This is an electron microscope image of the tensile fracture of a hot-pressed sintered sample of a 1% titanium-doped multilayer copper-based composite material. DETAILED DESCRIPTION

[0079] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0080] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0081] The equipment and instruments used in the following embodiments of the present invention include, but are not limited to: culture dishes, beakers, one thousandth precision electronic balance (model JS-15B), ultrasonic machine (model KQ-600DE), planetary ball mill (model WL-1), freeze dryer (SCIEMTZ-10N, the lowest temperature can reach -53 ° C), vacuum hot pressing sintering furnace (model VHP-V), wire cutting machine, universal mechanical testing machine, polishing machine, XRD, microscope, microhardness tester (model HXD-100TM / LCD).

[0082] The reagent raw materials used in the following examples of the present invention include: 300 mesh copper powder, purity ≥ 99.7%, density 8.9g / cm 3 ; 200 mesh titanium powder, purity ≥99.5%, density 4.50g / cm 3 ; Al2O3 whiskers, diameter 0.1-4μm, length 5-30μm, purity ≥99.85%, density 3.99g / cm 3 Graphene, 200 mesh, density 2.2g / cm 3 .

[0083] Example 1 Multilayer structure titanium-doped copper-based composite material

[0084] according to Figure 1 The process flow shown is to prepare a multilayer titanium-doped copper-based composite material.

[0085] S1. Evenly mix copper powder and 1wt% Al2O3 whiskers to prepare 50g of alumina whisker reinforced copper layer raw material. Evenly mix copper powder and 0.5wt% graphene to prepare 50g of graphene reinforced copper layer raw material. Evenly mix copper powder and 1wt% Ti powder to prepare 50g of titanium-doped copper layer raw material, and repeat three times for a total of 150g. After the materials are evenly mixed, put them into culture dishes respectively, add a small amount of alcohol (just enough to completely submerge the raw material powder), cover with plastic wrap, and put them into an ultrasonic machine for ultrasonic treatment for 30 minutes. Pay attention to control the water level in the ultrasonic instrument tank to be higher than the alcohol liquid level in the culture dish to ensure consistent ultrasonic effect.

[0086] S2. The raw material powders treated with ultrasound are respectively loaded into different agate jars, and then agate balls are added for ball milling, with a ball-to-material ratio of 3:1. In this embodiment, each raw material is 50g, so the corresponding agate balls are 150g. After adding the agate balls, a small amount of alcohol is added (to ensure that the alcohol can submerge the bottom layer of agate balls but not more than all agate balls). During the ball milling process, pay attention to observation and strictly prevent alcohol from overflowing from the mouth of the agate jar (causing raw material loss). Set the ball milling speed to 300 rpm, ball mill for 3 hours, and rotate forward for the first half hour and reverse for the last half hour.

[0087] S3. After the ball milling is completed, pour out the raw materials in the ball mill. Since a large amount of raw materials are attached to the agate balls, put the agate balls in an empty petri dish, rinse the agate balls with a small amount of alcohol, and then combine the alcohol used to rinse the agate balls with the ball milled materials. If there is residual powder material in the agate tank, rinse it with a small amount of alcohol and combine the rinse liquid.

[0088] S4. Let the material obtained in S3 and the culture dish air-dry for 24 hours until the alcohol in the material is fully volatilized and the material is converted into a dry powder or a state of distinct particles. Then, cover the culture dish with plastic wrap, poke a few small holes in the plastic wrap, and put it into the freeze dryer for freeze drying for 24 hours. Freeze drying: Turn on the refrigeration first, wait until the temperature reaches below -30℃, turn on the vacuum pump, and observe carefully in the first half an hour after putting it in. If there is residual alcohol in it, it will cause powder spraying. You need to stop the machine in time, let the material continue to air dry naturally, and then freeze dry it.

[0089] S5. After freeze-drying is completed, take out the material and prepare the mold. First, spread 25g of pure copper powder on the bottom layer of the mold, and tamp the powder with a cylinder; then add 50g of freeze-dried titanium-doped copper layer raw material and tamp it; then add 50g of freeze-dried alumina whisker reinforced copper layer raw material and tamp it; then add 50g of freeze-dried titanium-doped copper layer raw material; tamp it, add 50g of freeze-dried graphene reinforced copper layer raw material mixed powder and tamp it; add 50g of freeze-dried titanium-doped copper layer raw material mixed powder and tamp it; finally, spread 25g of pure copper powder on the top layer and tamp it. The layered arrangement of materials in the mold after tamping is as follows: Figure 2 As shown in the figure, except for the copper layer thickness of the bottom layer and the surface layer, the thickness of each other layer is 1mm.

[0090] This step uses three 50g portions of titanium-doped copper layer raw materials, which are placed between the aluminum oxide whiskers and the graphene-reinforced copper layer to achieve the effect of fusing different reinforcement phase materials. During the compaction process, pay attention to compacting tightly enough and ensuring flatness.

[0091] S6. After the multi-layer samples are loaded and compacted, Figure 3 The process parameters are set as shown, and the furnace is loaded and fired. First, the atmospheric pressure in the furnace is evacuated to below 20pa, and then the temperature is raised to 300℃ at a rate of 10℃ / min. After keeping at 300℃ for 10min, the temperature is raised to 930℃ at a rate of 10℃ / min. When the temperature reaches 650℃, the pressure is gradually increased. When the pressure reaches 20Mpa, the pressure is kept unchanged. At this time, the temperature is about 700℃. Wait for the temperature to continue to rise to 930℃ and then keep it at 930℃ for 2 hours. When the insulation is over, turn off the heating power and wait for the furnace to cool down. When the cooling temperature reaches about 560℃ (the specific temperature is determined by the temperature when the pressurization is completed), turn off the pressurization. Then wait for the temperature to drop to room temperature and turn off all power supplies. The next day, the furnace is opened to take samples to obtain a multilayer copper-based composite material.

[0092] Microstructure test analysis

[0093] X-ray diffraction analysis (XRD): Using an XRD diffractometer, the atomic layer inside the pattern is bombarded with X-rays at high speed to generate light radiation, and then the atomic or molecular structure of the pattern can be analyzed based on the analysis of the X-ray diffraction pattern. Each layer of raw material powder prepared in step S1 of Example 1: Cu-Ti, Cu-Al2O3, Cu-Gpe (graphene) was subjected to XRD analysis.

[0094] The XRD analysis results of raw material powder are as follows Figure 5As shown in the figure, the five main peaks in the spectrum are all Cu peaks. From the three strong peaks of Cu (111), (200) and (220) crystal planes, there is no shift in the main peaks. However, no corresponding peaks were detected for Ti, Al2O3 and graphene, probably because their contents were too low.

[0095] The multilayer copper-based composite material prepared in step S6 of Example 1 was subjected to XRD detection using an XRD diffractometer. Since the sample has a multilayer structure, four points were selected from top to bottom on the longitudinal surface of the sample for micro-area XRD detection. The results are as follows: Figure 6 As shown, they are point1, point2, point3, and point4 on the figure. The results show that there are five main peaks, all of which are Cu peaks. There is no shift when corresponding to the (111) crystal plane and (200) crystal plane of the three strongest peaks of Cu, but there is an obvious left shift when corresponding to the peak (220) crystal plane, and the shift is more obvious on the subsequent (311) crystal plane and (222) crystal plane. The reason for this phenomenon should be that the reinforcing phase elements combine with the Cu crystal during the sintering process and distort, thereby increasing the lattice constant.

[0096] Scanning electron microscope microanalysis (SEM): Using the secondary electron imaging technology of the scanning electron microscope, a very fine high-energy electron beam is used to scan the surface of the sample to stimulate the physical information of the test sample and obtain the surface morphology characteristics of the sample.

[0097] The materials of aluminum oxide whiskers and copper powder ball milling were analyzed by scanning electron microscope. Figure 7 As shown, the SEM image of the powder raw material after Al2O3 whiskers and copper powder were mixed with ultrasonic and ball milled. Figure 7 (a) is a picture of the Al2O3 whisker morphology, where the long morphology of the whisker can be clearly seen. Figure 7 (b) shows that the copper particles undergo plastic deformation after ball milling, changing from spherical particles to elliptical shapes. Al2O3 whiskers are distributed on the surface and inside of the copper particles, indicating that after ball milling, the Al2O3 whiskers and copper powder have been repeatedly rolled and deformed into a mixture. This shows that ball milling has achieved the ideal effect. Figure 8 It can be seen that the Al content at position 20 of the spectrum is 38.66 (wt%), and there is also distribution of graphene.

[0098] Figure 8 The element analysis results at 20 points in the spectrum are as follows:

[0099]

[0100]

[0101] The mixture of the ball-milled graphene powder and copper powder was scanned and analyzed using SEM. The results are as follows: Fig. 9 As shown. The SEM of the powder after ultrasonic ball milling of graphene powder and copper powder shows that Fig. 9 (a) is the SEM image of graphene morphology. It can be seen that at a magnification of 10,000 times, the overall graphene morphology is irregularly dispersed and shaped like wood ear. Fig. 9 (b) When observing the overall powder at 1000 times magnification, it can be seen that fine graphene is distributed around the large copper powder, and the overall distribution is relatively uniform.

[0102] The ball-milled Cu powder and Ti powder mixture was scanned and analyzed using SEM. The results are as follows: Fig.10 As shown in the SEM scanning image of Cu powder and Ti powder mixed after ultrasonic ball milling, Fig.10 (a) The larger particles with obvious deformation are Cu particles, while the smaller and more evenly distributed particles are Ti particles. Fig.10 (b) EDS analysis of copper-titanium powder. Analysis of point 23 in the spectrum shows that the Ti content at this point is 89.09 (Wt%).

[0103] Fig.10 The element analysis results at 23 points in the spectrum are as follows:

[0104] element Wt% At% Ti 89.09 75.12 Cu 2.50 1.59

[0105] In the experiment, the sample was cut into a 10×10mm rectangular pattern, one side was polished with sandpaper, then polished with a polishing machine, cleaned with nitric acid corrosive alcohol, and then metallographic observation was performed using a microscope. Since the prepared titanium-doped multilayer copper-based composite material was prepared, XRD analysis and testing were performed on each layer of the multilayer copper-based composite material.

[0106] First, the copper-graphene layer was analyzed by XRD. Fig.11 As shown in Figure 1, the XRD spectrum of the graphene-enhanced phase layer of the sintered bulk copper-based composite material. The sample was subjected to backscattering analysis, and the results were as follows: Fig.11 As shown, the backscattered EDS analysis of the copper-graphene mixed layer. Since graphene cannot be directly analyzed by spectroscopy, it can only be judged by the C content. The C content at the measured point is 67.22Wt%, and the Cu content is 29.97Wt%. Backscattered EDS results of copper-graphene layer Fig.11 The elemental analysis results of spectrum 1 in are as follows.

[0107] element Wt% At% C 67.22 89.63 O 2.81 2.82 Cu 29.97 7.55

[0108] Then, the copper-titanium layer was subjected to XRD analysis, and the results were as follows: Fig.12As shown in the backscattered EDS analysis of the copper-titanium layer, according to the line scan results, the dark shadow area is Ti element, and the two sides are Cu element. There are also some small black dots distributed in the non-shaded part, so there is also Ti element distribution in those areas.

[0109] like Fig.13 The backscattered EDS analysis of the copper-aluminum oxide layer shown in the figure shows that the small particles are Al2O3 whiskers. Figure 3 The content of AI in the site region is 22.35Wt%, the content of O is 21.72Wt%, and the content of Cu is 46.86Wt%.

[0110] The elemental analysis results are as follows.

[0111] element Wt% At% C 9.07 20.54 O 21.72 36.90 Al 22.35 22.52 Cu 46.86 20.04

[0112] Conclusion: In Example 1, a titanium-doped multilayer copper-based composite material was prepared by a powder metallurgy method. The sample was microscopically characterized by scanning electron microscopy and X-ray diffraction analysis, and then tensile, compression and hardness tests were performed using a universal mechanical testing machine to confirm that the copper-based composite material has a multilayer structure.

[0113] Combined with the microscopic characterization observation, it can be seen that the material has obvious stratification phenomenon, with Cu-Ti aggregation areas and Cu-Al2O3-Graphene concentrated areas. The preparation process effectively realizes the multi-layer structure. Combined with the mechanical properties test results, it can be seen that the material has differential regional hardness characteristics and can be used in special working environments.

[0114] Example 2 Titanium-doped multilayer copper-based composite material

[0115] The method is basically the same as Example 1, except that the Ti content in the titanium-doped copper layer raw material is changed to 4% during the batching process. The rest of the preparation process is exactly the same, and the multilayer copper-based composite material is obtained by hot pressing and sintering.

[0116] The multilayer copper-based composite material prepared in Example 1-2 was obtained by hot pressing and sintering. Figure 4 The test specimen is prepared by processing into the shape shown and is set aside.

[0117] Test 1 Microhardness performance test

[0118] The multilayer copper-based composite material prepared in Example 1-2 was subjected to a hardness test using a micro-Vickers hardness tester, with a load of 300N and a holding time of 10s. A rectangular test sample with smooth and flat upper and lower surfaces was placed on a hardness table. According to the different sizes of the indentations formed by the indenters at different hardnesses, the four vertices of the indentation were marked by the four-point method, and the hardness of the sample was calculated according to the Vickers hardness.

[0119]

[0120] During the test, a line was determined on the longitudinal surface of the sample (the surface of the multi-layer structure), and the test started from the edge to the other edge, with a total of 8 test points, with point 1 as the starting point and point 8 as the end point, representing the upper and lower edges of the sample respectively. The test results are shown in the following table.

[0121] Table 1 Sample hardness (HV)

[0122] The results show that most areas of the 1% titanium-doped multilayer copper-based composite material are in the 50-60HV range, but there are 70-76HV hardness points near the edges, which is related to the multilayer structure design. The main components of the areas near the two sides are copper powder and titanium powder mixed powder, and the area near the middle is copper powder, titanium powder, graphene doping and Al2O3 whisker doping. The hardness test results show that the sample forms a multilayer structure.

[0123] The hardness of the 4% titanium-doped multilayer copper-based composite material sample is between 70-80HV in most areas, but there will be a higher hardness of about 80-100HV near the two sides, and the highest hardness is 117HV near the lower edge. This is because during hot pressing and sintering, the Ti and Al2O3 whiskers and graphene in the middle part melt and rearrange to produce uneven distribution, but the distribution of Al2O3 whiskers and graphene is mostly in the area near the middle. Due to the layered structure characteristics of graphene, clusters are prone to appear in composite materials, which has an adverse effect on the overall performance of the composite material to a certain extent. Therefore, the local hardness of the material has decreased. The same Al2O3 whisker long diameter morphology is also prone to aggregation and negative impact. Through the multilayer structure setting and the use of titanium-doped copper layer spacing setting, this clustering or aggregation effect has been improved to a certain extent, and the overall performance is relatively good.

[0124] Overall, the average hardness of the 1% titanium-doped copper-based composite material is 60.877HV, and the average hardness of the 4% titanium-doped copper-based composite material is

[0125] Serial number\site 1 2 3 4 5 6 7 8 1(1%Ti) 53.91 72.642 55.173 55.038 54.639 59.966 60.154 75.679 2(4%Ti) 73.56 104.86 83.46 86.32 93.40 77.21 117.32 78.22

[0126] The hardness of the copper-based composite material doped with 4% titanium is 89.298HV, and the average hardness increases by 46.68%. The hardness of the copper-based composite material doped with 4% titanium is higher than that of the copper-based composite material doped with 1% titanium. Within a certain dosage range, the hardness of the copper-based composite material is significantly improved with the increase of titanium content.

[0127] Test 2: Compressive strength performance test

[0128] The compressive strength of the sample was tested using a universal mechanical testing machine. During the compression process, a cylinder with a diameter of D = 5 mm and a height of L = 13 mm, which was smooth and flat on the upper and lower surfaces, was placed in the compressor and compressed at a speed of 0.5 mm / s. Three test samples were prepared for each example sample for compression to measure the compressive strength, and the average value was taken after three tests.

[0129] Among them, the compressive load-displacement of 1% titanium-doped copper-based composite samples is as follows Fig.14 The results show that the maximum loads of the samples are 5.5643KN, 6.5824KN, and 4.4101KN, and the maximum compressive strengths are 285MPa, 335MPa, and 225MPa, respectively.

[0130] In the experiment, the bottom surface of sample No. 3 was not flat enough, so it was bent in one direction at the beginning of the compression test, and the measured compressive strength was the lowest (only 225MPa). If this data is removed, the average compressive strength of the 1% titanium-doped sample is 310MPa.

[0131] Compressive load-displacement of 4% titanium-doped copper matrix composite samples Fig.15 As shown. The results show that the maximum loads of the samples are 7.369KN, 7.9258KN, and 6.9138KN, and the maximum compressive strengths are 375MPa, 405MPa, and 350MPa, respectively. The average maximum compressive strength of the 4% titanium-doped sample is 376.66MPa. In general, the maximum compressive strength of the 4% titanium-doped sample is slightly greater than that of the 1% titanium-doped sample, and the average compressive strength has increased by 34.04%.

[0132] Table 2 Average compressive strength of copper-based composite materials (unit: MPa)

[0133] Serial number\site #1 #2 #3 average value Standard Deviation 1(1%Ti) 285 335 225 281 44.969 2(4%Ti) 375 405 350 376.66 22.484

[0134] Test 3: Tensile strength performance test

[0135] The tensile strength of the sample was tested using a universal mechanical testing machine. The longitudinal tensile strength of the multilayer copper-based composite material sample needs to be tested. A small tensile die with a rated load of 10KN was used to stretch the test sample of Example 1-2 prepared above at a speed of 0.5mm / s, and the average value was taken as the tensile strength of the sample.

[0136] like Fig.16 As shown in the tensile force-displacement diagram of the 1% titanium-doped sample prepared in Example 1, there are two test samples. According to the results, the maximum tensile forces of the two samples are 301.4259N and 299.4462N, respectively, and the tensile strengths are 33MPa and 29MPa, respectively, with an average tensile strength of 31MPa.

[0137] like Fig.17 As shown in the tensile force-displacement diagram of the 4% titanium-doped sample prepared in Example 2, there are four test samples. According to the results, none of the four samples were broken. The test was stopped when the pure copper layer was deformed. The maximum tensile forces were: 1506.06N, 1306.71N, 1023.14N, 4308.92N (the last set of data is supplementary experimental data and is not shown in Fig.17 The tensile strengths are 199MPa, 163MPa, 148MPa, 308MPa, and the average tensile strength is 204.5MPa. Due to the large fluctuations in the final supplementary test data, attention should be paid to strengthening the unified standardization of test samples in subsequent tests to reduce test errors.

[0138] Then another set of experiments was added, and the specimens were broken at the pure copper layer. The maximum tensile force was 2144.73N and the tensile strength was 308MPa.

[0139] Table 3 Tensile strength of samples

[0140] #1 #2 #3 #4 average value Standard Deviation 1% 33MPa 29MPa \ \ 31MPa 2 4% 199MPa 163MPa 148MPa 308MPa 204.5MPa 51.75

[0141] It can be seen that the average tensile strength of the 1% titanium-doped sample prepared in Example 1 is 31 MPa, and the average tensile strength of the 4% titanium-doped sample prepared in Example 2 is 204.5 MPa. As the Ti content increases, the average tensile strength increases by 559.68%.

[0142] After the tensile test, the sample was subjected to fracture analysis. The tensile fracture of the 1% titanium-doped sample was as follows: Fig.18 As shown, (a), (b), (c), and (d) correspond to 10,000, 20,000, 5,000, and 200 times magnification, respectively. The tensile fracture shows that the fracture is generally flat from the SEM scan with a magnification of 200 times, and the presence of dimples can be seen. According to the SEM scan photo with a magnification of 5,000 times, a flow pattern can be seen, and there is a cleavage fracture during the fracture process, and the fracture that occurs is a brittle fracture.

[0143] Discussion and analysis of strengthening mechanism: According to the above mechanical properties tests, the titanium-doped multilayer copper-based composites prepared experimentally have significantly improved mechanical properties compared with single copper. Since the nano-scale aluminum oxide whiskers and graphene are evenly dispersed after ball milling, the dispersion strengthening effect hinders the growth of copper particles and produces a grain refinement effect. At the same time, when aluminum oxide whiskers and graphene are distributed around copper particles, there are small-scale clusters and aggregation phenomena, which will form strong resistance when dislocations occur, preventing the occurrence of dislocations. At the same time, these clusters will have the effect of other load transfer, so that the load is transferred to the titanium reinforcement phase with better mechanical properties, thereby improving the load bearing capacity.

[0144] Test 4 Density test

[0145] The Archimedes displacement method is used to test the density of the sample. The first measurement is to place the sample block on the upper balance to measure the mass. When it is displayed as M1, press the enter key. After the interface jumps to M2, put the sample into the water balance. After the number is stable, press the enter key again to measure the actual density of the object. After the measurement is completed, calculate according to the following formula.

[0146] F 浮力 =ρ 水 V 排 =M3g-M3g

[0147]

[0148] Then, the theoretical density of the sample can be calculated based on the ratio design of the experimental sample, and then the density can be calculated according to the following formula.

[0149]

[0150] The theoretical density of the 1% titanium doped sample is 8.8836 g / cm 3 , the density of the 4% titanium doped sample is 8.8181 g / cm 3 According to the actual density calculation, the corresponding densities of Example 1 and Example 2 are 96.11% and 96.54% respectively. The density of the two samples is not much different, and the overall density is about 96%. The specific reason is the clustering phenomenon of graphene and the aggregation phenomenon of whiskers, as well as the deformation of Ti element and Cu.

[0151] Table 4 Theoretical density of copper-based composite material specimens (g / cm 3 )

[0152] Serial number Cu Ti <![CDATA[Al2O3]]> GPE Theoretical density Actual density Density 1%Ti 8.8531 0.0225 0.006384 0.00168 8.8836 8.5388 96.11% 4%Ti 8.7193 0.0908 0.006384 0.00168 8.8181 8.5137 96.54%

[0153] The above density test results show that the density of the copper-based composite material has little to do with the amount of titanium doping. The titanium-doped multilayer copper-based composite material prepared according to the preparation process of the present invention exhibits good density, and the quality of fusion of multiple components is high.

[0154] Test 5 Friction Test:

[0155] The friction performance of the titanium-doped copper-based composite material prepared in Example 1-2 was tested using a high-temperature reciprocating friction and wear tester (GF-I).

[0156] The friction performance test was carried out using a high temperature reciprocating friction and wear tester (GF-I). The test conditions were 500r / min, load 20N, one-way 5mm, time 40min, and wear loss 0.1-0.3mm. 3 The results show that the friction properties of the titanium-doped copper-based composite materials prepared in Examples 1-2 are anisotropic.

[0157]

[0158] The titanium-doped copper-based composite material prepared in Example 1-2 was subjected to grinding and polishing treatment, and the friction properties of different layers were detected and analyzed respectively.

[0159] Example 3 Titanium-doped multilayer copper-based composite material

[0160] Titanium-doped multilayer copper-based composite material is prepared in the following steps:

[0161] Weigh the raw materials of titanium doped layer, aluminum oxide whisker reinforcement layer and graphene reinforcement layer according to the designed proportion. Mix aluminum oxide whisker and copper powder evenly to prepare a mixed powder with an aluminum oxide whisker content of 2wt%, and obtain the raw material of aluminum oxide whisker reinforcement layer. Mix graphene and copper powder evenly to prepare a mixed powder with a graphene content of 1.5wt%, and obtain the raw material of graphene reinforcement layer. Mix titanium powder and copper powder evenly to prepare a mixed powder with a titanium powder content of 2wt%, and obtain the raw material of titanium doped layer. Place the above raw materials in a culture dish respectively, add alcohol to completely submerge the materials, and perform ultrasonic dispersion treatment for 30 minutes. After the ultrasonic treatment, the raw material powders are respectively loaded into agate jars for ball milling; during the ball milling process, the ball-to-material ratio is 3:1; alcohol is added to submerge the agate balls at the bottom layer, but not all the agate balls. The ball milling speed is 300 rpm, and the ball milling is 3 hours. The ball milling process is half forward and half reverse, alternating.

[0162] After the ball milling is completed, take out the raw materials and rinse the agate balls with alcohol, and combine the raw material powders. Put them into a petri dish and use natural air drying to evaporate and remove the alcohol. The natural air drying time is 24 hours. When the raw material powder in the petri dish is dried to a state of distinct particles, cover the petri dish with plastic wrap; poke at least one hole in the plastic wrap, and then put the raw material powder and the petri dish into a freeze dryer and freeze-dry for 24 hours.

[0163] After freeze drying, graphite paper is placed in the sintering mold to prevent the inner wall of the mold from directly contacting the composite powder and forming adhesion. Spread a layer of pure copper powder on the bottom of the mold and compact the powder; then add titanium doping layer raw materials, aluminum oxide whisker reinforcement layer raw materials, titanium doping layer raw materials, graphene reinforcement layer raw materials, titanium doping layer raw materials, and pure copper powder in sequence; after each addition of raw materials, compaction is performed to ensure that the materials are tight and flat. In addition to pure copper powder, the thickness of each layer of titanium doping layer raw materials, aluminum oxide whisker reinforcement layer raw materials, and graphene reinforcement layer raw materials is 2mm. After each material is added to the mold, it is compacted separately.

[0164] Hot pressing sintering is carried out, and the sintering process is as follows: first evacuate to below 20Pa, then heat up to 300℃ at a rate of 10℃ / min, and keep warm for 20min; then heat up to 930℃ at a rate of 10℃ / min. At the same time, when the temperature reaches 650℃, gradually pressurize, and when the pressure reaches 20Mpa, keep the pressure; after the temperature rises to 930℃, keep the heat and pressure and sinter for 2.5 hours. After the heat preservation and pressure sintering is completed, turn off the heating power and cool with the furnace; turn off the pressure when the temperature cools to 700℃. Then, turn off all power supplies after cooling to room temperature, open the furnace and take samples after 24 hours to obtain a titanium-doped multilayer copper-based composite material.

[0165] The prepared titanium-doped multilayer copper-based composite material was subjected to a performance test. The test was conducted using the same method as in "Test 1 Microhardness Performance Test". The results showed that the titanium-doped layer with a titanium doping amount of 4wt% prepared in Example 3 made the hardness of the multilayer copper-based composite material perform well, and the amount of the reinforcing phase aluminum oxide whiskers / graphene was also relatively large, resulting in a better reinforcing effect. The hardness of the titanium-doped multilayer copper-based composite material reached an average value of 93.81±11.67HV.

[0166] The same test methods as "Test 2 Compressive Strength Performance Test" and "Test 3 Tensile Strength Performance Test" were used for testing. The compressive strength of the titanium-doped multilayer copper-based composite material is 376.67±38.84MPa, and the average tensile strength is 173.67±16.22MPa. The results show that the average compressive strength and average tensile strength of the composite material with 4% titanium addition are good. It is speculated that there is solid solution strengthening of Cu and Ti, forming more solid solution structures, and at the same time, the reinforcing phases of alumina whiskers and graphene reinforcing phases are more evenly dispersed in the copper matrix, making it difficult for dislocations to expand and hindering the movement of dislocations. The combination of the two significantly increases the strength of the material.

[0167] The same method as "Test 4 Density Test" was used for testing. The actual density was 7.9625 g / cm 3 , the density of multilayer copper-based composite materials is slightly lower than that of pure copper, indicating that there is still room for improvement in the density of hot-pressed sintering materials.

[0168] The same method as in "Test 5 Friction Test:" was used for the test. The friction performance test was conducted using a high temperature reciprocating friction and wear tester (GF-I). The test conditions were 500 r / min, 5 mm per stroke, 40 min, and a wear loss of 0.1 to 0.4 mm. 3 The measured stable friction coefficient of the multi-layer copper-based composite material is 0.6-0.7 for a load of 10N, 0.58-0.62 for a load of 20N, and 0.6-0.62 for a load of 30N.

[0169] Test 6 Temperature-dependent resistivity test

[0170] The resistivity of the samples was tested at 25-500°C using a Seebeck coefficient and resistance measurement system (LSR-3 / 1100). The resistivity of the 1% Ti sample varied between 0.026 and 0.083 μΩ*m, the resistivity of the 2% Ti sample varied between 0.047 and 0.11 μΩ*m, and the resistivity of the 4% Ti sample varied between 0.060 and 0.12 μΩ*m. The resistivity increased slightly with the increase of Ti doping, and the resistivity of the sample increased slightly with the increase of the test temperature.

[0171] Test 7 Thermal Expansion Coefficient at Variable Temperature

[0172] The thermal diffusion coefficient of the samples was tested at 25-500°C using a laser thermal conductivity analyzer (LINSEIS LFA1000). The thermal diffusion coefficient of the 1% Ti sample was between 0.686 and 0.594 cm 2 / s, the thermal diffusion coefficient of the 2% Ti sample is 0.483~0.437cm 2 / s, the resistivity of the 4% Ti sample is between 0.390 and 0.406 cm 2 / s. With the increase of Ti doping, the thermal diffusion coefficient increases slightly, and with the increase of test temperature, the thermal diffusion coefficient decreases slightly.

[0173] Example 4

[0174] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 6%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that of Example 3.

[0175] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 402.17±36.24 MPa, tensile strength 174.56±19.14 MPa, hardness 88.1 HV, and friction coefficient 0.52-0.61.

[0176] Example 5

[0177] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 3%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that of Example 3.

[0178] The properties of the prepared titanium-doped multilayer copper-based composite material are as follows: compressive strength 321.62±35.38MPa, tensile strength 75.13±18.26MPa, hardness 76.7HV, and friction coefficient 0.61-0.71.

[0179] Example 6

[0180] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0181] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 382.90±38.22MPa, tensile strength 165.80±16.51MPa, hardness 85.3HV, and friction coefficient 0.55-0.63.

[0182] Example 7

[0183] Refer to Example 3 for a method of preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.8%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0184] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 375.62±33.75MPa, tensile strength 161.93±19.32MPa, hardness 96.2HV, and friction coefficient 0.53-0.62.

[0185] Example 8

[0186] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.2%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0187] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 382.45±38.21 MPa, tensile strength 172.47±18.92 MPa, hardness 96.6 HV, and friction coefficient 0.52-0.63.

[0188] Example 9

[0189] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 0.8%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0190] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 280.86±28.52MPa, tensile strength 43.48±13.87MPa, hardness 93.1HV, and friction coefficient 0.61-0.65.

[0191] It can be seen from the performance test results of the multilayer copper-based composite materials prepared in Examples 4 to 9 that when the content of alumina whiskers changes, the compressive properties and tensile strength of the composite materials are better. If the addition amount of the alumina whisker reinforcement layer is controlled at 1%-2.0%, the strength is higher. If the amount of alumina whiskers exceeds 3%, there will be a certain loss. This may be because the alumina whiskers form agglomerations, which makes it easy for structural defects to grow, which is not conducive to the improvement of strength.

[0192] Example 10

[0193] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 2.5%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 1.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0194] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 326.90±35.86MPa, tensile strength 67.67±17.37MPa, hardness 69.7HV, and friction coefficient 0.53-0.62.

[0195] Embodiment 11

[0196] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 1.5%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 1.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0197] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 389.97±46.60 MPa, tensile strength 156.86±15.60 MPa, hardness 91.6 HV, and friction coefficient 0.52-0.62.

[0198] Example 12

[0199] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 1%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 1.5 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0200] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 378.46±45.36MPa, tensile strength 164.73±14.76MPa, hardness 96.7HV, and friction coefficient 0.51-0.63.

[0201] Example 13

[0202] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 0.8%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 1.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0203] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 375.31±41.25 MPa, tensile strength 169.31±35.21 MPa, hardness 80.3 HV, and friction coefficient 0.52-0.64.

[0204] Embodiment 14

[0205] Refer to Example 3 for a method of preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 2%, the graphene content in the graphene reinforcement layer raw material is 0.6%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 1.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0206] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 369.20±40.59 MPa, tensile strength 175.76±17.50 MPa, hardness 83.6 HV, and friction coefficient 0.53-0.61.

[0207] From the performance test results of the multilayer copper-based composite materials prepared in Examples 10 to 14, it can be seen that when the graphene content of the graphene-enhanced phase layer in the material increases, the performance can be enhanced to a certain extent, but too much graphene performance slip layer, on the contrary, reduces the material performance and the friction coefficient, which may be due to the segregation of the material. It is a good choice to control the graphene content of the graphene-enhanced layer within 1.5%, and the optimal amount range of graphene can be further studied.

[0208] Embodiment 15

[0209] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 1.5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0210] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 301.19±36.12 MPa, tensile strength 154.90±15.41 MPa, hardness 66.3 HV, and friction coefficient 0.52-0.63.

[0211] Example 16

[0212] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 2.5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that of Example 3.

[0213] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 345.49±31.05MPa, tensile strength 174.84±19.14MPa, hardness 76.7HV, and friction coefficient 0.51-0.61.

[0214] Embodiment 17

[0215] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 3.5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0216] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 378.98±45.36MPa, tensile strength 173.25±17.32MPa, hardness 74.5HV, and friction coefficient 0.52-0.62.

[0217] Embodiment 18

[0218] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4.5%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of each layer is in the range of 2 mm. The hot pressing sintering process procedure is consistent with that in Example 3.

[0219] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 405.96±44.55 MPa, tensile strength 182.30±18.21 MPa, hardness 89.6 HV, and friction coefficient 0.57-0.62.

[0220] It can be seen from the experimental results of Examples 15 to 18 that when the amount of titanium powder in the titanium-doped layer increases, the comprehensive performance of the material will be improved, which is consistent with the results of the studies in Examples 1 and 2. Increasing titanium powder can achieve better improvement in the interlayer interface, so a titanium doping amount ≥ 3.5% is a more preferred range.

[0221] Embodiment 19

[0222] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.6%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is spread on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 1.8 mm, the thickness of the graphene reinforcement layer is 1.5 mm, and the thickness of each titanium-doped layer is 1.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0223] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 415.43±49.82MPa, tensile strength 172.46±17.24MPa, hardness 89.8HV, friction coefficient 0.54-0.64.

[0224] Embodiment 20

[0225] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.6%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is spread on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 1.8 mm, the thickness of the graphene reinforcement layer is 1.5 mm, and the thickness of each titanium-doped layer is 1.0 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0226] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 435.66±43.50 MPa, tensile strength 169.60±18.59 MPa, hardness 94.6 HV, and friction coefficient 0.53-0.63.

[0227] Embodiment 21

[0228] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.6%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is spread on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 1.8 mm, the thickness of the graphene reinforcement layer is 1.5 mm, and the thickness of each titanium-doped layer is 0.8 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0229] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 442.57±48.62MPa, tensile strength 182.29±16.38MPa, hardness 92.7HV, and friction coefficient 0.54-0.64.

[0230] Embodiment 22

[0231] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.6%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 1.8 mm, the thickness of the graphene reinforcement layer is 1.5 mm, and the thickness of each titanium-doped layer is 0.5 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0232] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 412.28±45.32MPa, tensile strength 175.27±25.75MPa, hardness 92.9HV, and friction coefficient 0.52-0.62.

[0233] In the tests of Examples 19 to 22, the thickness range of the titanium-doped layer was adjusted. The results showed that when the thickness of the titanium-doped layer was reduced, the overall structural strength of the copper-based composite material increased. In particular, when the thickness was selected in the range of 0.5-1 mm, the compressive strength and tensile strength of the material were both good, which may be due to the relatively increased ratio of the thickness of the reinforcement phase layer, which improved the overall multilayer structure.

[0234] Embodiment 23

[0235] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1.2%, and the titanium powder content in the titanium-doped layer raw material is 4.2%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is laid on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 2 mm, the thickness of the graphene reinforcement layer is 2 mm, and the thickness of each titanium-doped layer is 1.0 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0236] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 423.28±46.53 MPa, tensile strength 174.21±15.66 MPa, hardness 94.1 HV, and friction coefficient 0.51-0.61.

[0237] Embodiment 24

[0238] Refer to Example 3 for a method for preparing a titanium-doped copper-based composite material, the only difference being that the raw material mixed powder ratio is as follows: the aluminum oxide whisker content in the aluminum oxide whisker reinforcement layer raw material is 1.5%, the graphene content in the graphene reinforcement layer raw material is 1%, and the titanium powder content in the titanium-doped layer raw material is 4.2%. During the preparation process, the arrangement order of each layer is the same as in Example 3, a layer of pure copper powder is spread on the bottom of the mold, and the powder is compacted; then the titanium-doped layer raw material, the aluminum oxide whisker reinforcement layer raw material, the titanium-doped layer raw material, the graphene reinforcement layer raw material, the titanium-doped layer raw material, and the pure copper powder are added in sequence. The thickness of the aluminum oxide whisker reinforcement layer is 2 mm, the thickness of the graphene reinforcement layer is 2 mm, and the thickness of each titanium-doped layer is 1.1 mm. The hot pressing sintering process procedure remains consistent with that of Example 3.

[0239] The prepared titanium-doped multilayer copper-based composite material was tested using the same method as above, and the properties were as follows: compressive strength 432.14±47.52 MPa, tensile strength 173.49±17.35 MPa, hardness 95.6 HV, and friction coefficient 0.51-0.61.

[0240] Compared with the cases of Examples 20-22, Examples 23 and 24 increase the thickness of the aluminum oxide whisker reinforcement layer and the graphene reinforcement layer, and also increase the thickness of the titanium doped layer. The performance of the structural material is also greatly improved. The enhanced phase layer and the titanium doped layer should have a certain degree of mutual fusion and penetration during the hot pressing sintering process. After increasing the thickness of the enhanced phase layer, the performance improvement of the enhanced phase of the multilayer structure is improved. At the same time, the thickness ratio of the titanium doped layer as a transition layer is correspondingly increased, and the comprehensive performance of the material is enhanced. On the whole, the titanium doped layer thickness is selected to be 0.8-1.1:1.5-2 as the ratio of the thickness of the enhanced phase layer, which can maximize the transition fusion of the titanium doped layer to the enhanced phase layer, ensure the interface bonding performance of the enhanced phase, and maximize the special strengthening effect of the enhanced phase.

Claims

1. A titanium-doped multilayer copper-based composite material, characterized in that: It comprises a titanium-doped layer, a reinforced phase composite layer, and a copper-based surface layer; the titanium-doped layer is a copper-titanium alloy layer doped with 1-6wt% titanium; the reinforced phase composite layer is a composite layer with copper as the main body and 0.2-2wt% of the reinforced phase material; The titanium-doped multilayer copper-based composite material is provided with the following structural layers in order from bottom to top: a first copper-based surface layer, a second titanium-doped layer, a third graphene reinforcement layer, a fourth titanium-doped layer, a fifth aluminum oxide whisker reinforcement layer, a sixth titanium-doped layer, and a seventh copper-based surface layer; The thicknesses of the titanium doped layer, the reinforced phase composite layer, and the copper-based surface layer are independent of each other and are all within the range of 0.5-3 mm; The reinforced phase composite layer is at least one of an aluminum oxide whisker reinforced layer and a graphene reinforced layer; The copper-based surface layers are located at the uppermost and lowermost layers of the composite material.

2. The titanium-doped multilayer copper-based composite material according to claim 1, characterized in that: The thickness of each layer was controlled to be 1.4-2.1 mm.

3. The method for preparing a titanium-doped multilayer copper-based composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Weigh the raw materials of the titanium doped layer, the aluminum oxide whisker reinforcement layer and the graphene reinforcement layer according to the designed proportion; The aluminum oxide whisker and copper powder are mixed evenly to obtain an aluminum oxide whisker reinforcement layer raw material; The graphene and copper powder are mixed evenly to obtain a graphene reinforcement layer raw material; Mixing titanium powder and copper powder evenly to obtain a titanium doped layer raw material; Add the above raw materials into alcohol respectively, completely submerge the materials, and perform ultrasonic dispersion treatment; S2. After the ultrasonic treatment, the raw material powders are respectively put into agate jars for ball milling; alcohol is added to ensure that the alcohol submerges the bottom layer of agate balls but does not submerge all agate balls; S3. After the ball milling is completed, the raw materials are taken out and the agate balls are rinsed with alcohol, and the raw material powders are combined; S4, putting the raw material powder into a culture dish, and letting it stand to evaporate and remove the alcohol; when the raw material powder in the culture dish is dried to a state of distinct particles, cover the culture dish with plastic wrap; Poke at least one hole in the plastic wrap, then place the raw powder and the petri dish into the freeze dryer for freeze drying; S5. After freeze drying, a layer of pure copper powder is spread on the bottom of the mold and the powder is compacted; then titanium doping layer raw material, aluminum oxide whisker reinforcement layer raw material, titanium doping layer raw material, graphene reinforcement layer raw material, titanium doping layer raw material, and pure copper powder are added in sequence; after each addition of raw materials, compaction is performed to ensure that the materials are compacted and flat; Except for pure copper powder, the thickness of each layer of titanium doped layer raw material, aluminum oxide whisker reinforcement layer raw material, and graphene reinforcement layer raw material shall not exceed 5mm; S6, hot pressing sintering, the sintering process is as follows: First, evacuate to below 20Pa, then heat up to 290-325℃ at a rate of 5-15℃ / min, keep warm for 5-25min; then heat up to 920-945℃ at a rate of 5-15℃ / min; At the same time, when the temperature reaches 640-655℃, gradually increase the pressure, and maintain the pressure when the pressure reaches 20Mpa; when the temperature rises to 930℃±10℃, keep the temperature and pressure and sinter for 2-2.5 hours; After the heat preservation and pressure sintering is completed, turn off the heating power supply and cool down with the furnace; when the temperature cools to 650-750℃, turn off the pressurization; Then, after the temperature drops to room temperature, all power supplies are turned off, and after 12-24 hours, the furnace is opened to take samples to obtain a titanium-doped multilayer copper-based composite material.

4. The method for preparing a titanium-doped multilayer copper-based composite material according to claim 3, characterized in that: In step S2, the ball milling speed is 300 rpm, and the ball milling is performed for 2-4 hours.

5. The method for preparing a titanium-doped multilayer copper-based composite material according to claim 3, characterized in that: In S1, sonicate for 20-40 minutes.

Citation Information

Patent Citations

  • Preparation method of graphene and aluminum oxide whisker co-reinforced copper-based composite material and product thereof

    CN110699617A

  • Preparation method of layered copper-based composite material

    CN111020260A